The effect of knowledge management practices on employees' innovative performance - Seyed Mohammadbagher Jafari; Mariyayee Suppiah (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
The subject of innovation has been considered an important factor that contributes to both growth and survival of mankind. Given the importance lead by innovation, researches from multiple disciplines have attempted to answer to some critical questions like "what can be done to improve innovation at the workplace?" The management of knowledge is commonly recognized as an important antecedent towards innovation. The importance in finding the best process oriented approach as well as best industrial practices of knowledge management has surged steadily over the period due to rapid globalization and the need for organizations to seek competitive advantage. However, it is often argued that too much formalization of the best practice could actually hinder creativity and innovation within the organization. This research paper is aimed to explore the influence of knowledge management practices on employees' innovative performance in an organization perspective. Knowledge management practices within an organization can be defined by; knowledge acquisition, knowledge dissemination and finally responsiveness towards knowledge. In order to test the influence of these variables on employees' innovative performance, seven hypotheses were developed based on the theoretical research framework. The quantitative survey approach was selected as the method to evaluate the significance of each hypothesis. The data collection results were from 384 usable questionnaires that had been previously distributed to multiple manufacturing firms in Malaysia. The results obtained from this research conclude that knowledge management plays a vital role on supporting employees' innovative performance within organizations. It also revealed that two types of knowledge management subcategories; knowledge acquisition and responsiveness to knowledge plays more significant role on encouraging employees' innovative performance in comparison with knowledge dissemination. The managerial implications and limitations of current study were also discussed in the paper.
Keywords: 650; Knowledge Management; Innovation; Employees'Performance; Best Practices; Malaysian Manufacturing Industries